The Relationship between Information and Communications Technology and Banking Stability in GCC Countries - Chiad, Faycal (Ekonomika, 2025)
With the great development in digitalization, ICT tools are increasingly being integrated into banking and financial services, reshaping the contemporary financial system. This study examines the impact of ICT on the banking stability in the Gulf Cooperation Council countries (GCC) from 2004 to 2023. This paper uses several econometrics methods (the fixed effects model, the system GMM, FMOLS, DOLS), and pairwise Dumitrescu causality tests. The study found that ICT is crucial in increasing banking stability. The coefficient of ICT is significantly positive, both when internet and mobile are used as explanatory variables. For instance, a 1% increase in mobile subscriptions (internet users) leads to approximately 0.012% (0.019%) increase in banking stability. Furthermore, the advantages of internet users outweigh those of mobile subscribers. The findings reveal the presence of significant positive relationship between economic growth, market capitalization, and banking stability. Whereas, cost to income has a negative impact on banking stability. These findings offer more insights into how ICT affects the stability of the banking industry.
Keywords: Internet; Mobile; banking; banking stability; Gulf Cooperation Council (GCC)